Simultaneous Quantification of Mitochondrial Mature Frataxin and Extra-Mitochondrial Frataxin Isoform E in Friedreich’s Ataxia Blood - Wang, Qingqing; Laboureur, Laurent; Weng, Liwei; Eskenazi, Nicolas M.; Hauser, Lauren A.; Mesaros, Clementina; Lynch, David R.; Blair, Ian A. (Frontiers in Neuroscience, 2022)
Friedreich’s ataxia (FRDA) is an autosomal recessive disease caused by an intronic guanine-adenine-adenine (GAA) triplet expansion in the frataxin (FXN) gene, which leads to reduced expression of full-length frataxin (1–210) also known as isoform 1. Full-length frataxin has a mitochondrial targeting sequence, which facilitates its translocation into mitochondria where it is processed through cleavage at G41-L42 and K80-S81 by mitochondrial processing (MPP) to release mitochondrial mature frataxin (81–210). Alternative splicing of FXN also leads to expression of N-terminally acetylated extra-mitochondrial frataxin (76–210) named isoform E because it was discovered in erythrocytes. Frataxin isoforms are undetectable in serum or plasma, and originally whole blood could not be used as a biomarker in brief therapeutic trials because it is present in erythrocytes, which have a half-life of 115-days and so frataxin levels would remain unaltered. Therefore, an assay was developed for analyzing frataxin in platelets, which have a half-life of only 10-days. However, our discovery that isoform E is only present in erythrocytes, whereas, mature frataxin is present primarily in short-lived peripheral blood mononuclear cells (PBMCs), granulocytes, and platelets, meant that both proteins could be quantified in whole blood samples. We now report a quantitative assay for frataxin proteoforms in whole blood from healthy controls and FRDA patients. The assay is based on stable isotope dilution coupled with immunoprecipitation (IP) and two-dimensional-nano-ultrahigh performance liquid chromatography/parallel reaction monitoring/high resolution mass spectrometry (2D-nano-UHPLC-PRM/HRMS). The lower limit of quantification was 0.5 ng/mL for each proteoform and the assays had 100% sensitivity and specificity for discriminating between healthy controls (n = 11) and FRDA cases (N = 100 in year-1, N = 22 in year-2,3). The mean levels of mature frataxin in whole blood from healthy controls and homozygous FRDA patients were significantly different (p < 0.0001) at 7.5 ± 1.5 ng/mL and 2.1 ± 1.2 ng/mL, respectively. The mean levels of isoform E in whole blood from healthy controls and homozygous FRDA patients were significantly different (p < 0.0001) at 26.8 ± 4.1 ng/mL and 4.7 ± 3.3 ng/mL, respectively. The mean levels of total frataxin in whole blood from healthy controls and homozygous FRDA patients were significantly different (p < 0.0001) at 34.2 ± 4.3 ng/mL and 6.8 ± 4.0 ng/mL, respectively. The assay will make it possible to rigorously monitor the natural history of the disease and explore the potential role of isoform E in etiology of the disease. It will also facilitate the assessment of therapeutic interventions (including gene therapy approaches) that attempt to increase frataxin protein expression as a treatment for this devastating disease.